1999
DOI: 10.1021/jm980703f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Boron-Containing Polyamines as Potential Agents for Neutron Capture Therapy of Brain Tumors

Abstract: New boron-containing spermidine/spermine (SPD/SPM) analogues have been synthesized: N5-[4-(2-aminoethyl-o-carboranyl)butyl] and N5-{4-[(2,3-dihydroxypropyl)-o-carboranyl]butyl} SPD/SPM derivatives (ASPD-5, ASPM-5, DHSPD-5, and DHSPM-5) as well as N5-{[4-(dihydroxyboryl)phenyl]methyl}spermidine (BBSPD-5). These boronated polyamines retain their ability to displace ethidium bromide from calf thymus DNA and are rapidly taken up in vitro by F98 rat glioma cells. The in vitro toxicities of ASPD-5, ASPM-5, DHSPD-5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 71 publications
2
44
0
Order By: Relevance
“…In general, the moderate toxicity of all of the nucleosides that were evaluated appears to have been related to their lipophilicity rather than to nucleoside metabolism. In previous studies involving carboranyl polyamines, carborane-dependent lipophilicity has been identified by us as the source of substantial in vitro and in vivo toxicity (59,60). The cause of this toxicity is still unknown, but it could be reduced partially by the attachment of additional hydrophilic groups to the polyamines.…”
Section: Boron Containing Nucleosides As Delivery Agents For Nctmentioning
confidence: 99%
“…In general, the moderate toxicity of all of the nucleosides that were evaluated appears to have been related to their lipophilicity rather than to nucleoside metabolism. In previous studies involving carboranyl polyamines, carborane-dependent lipophilicity has been identified by us as the source of substantial in vitro and in vivo toxicity (59,60). The cause of this toxicity is still unknown, but it could be reduced partially by the attachment of additional hydrophilic groups to the polyamines.…”
Section: Boron Containing Nucleosides As Delivery Agents For Nctmentioning
confidence: 99%
“…Some examples are derivatives of aziridines, acridines, phenanthridines (compound 6), trimethoxyindoles, carboranylpolyamines, Pt(II)-amine complexes, di-and tribenzimidazoles (66)(67)(68)(69). A limitation of boron-containing polyamines is their frequently observed in vitro and in vivo toxicity, although promising derivatives with low cytotoxicity have been synthesized (70)(71)(72)(73). Other nuclear-targeting molecules are nido-carboranyl oligomeric phosphate diesters (OPDs).…”
Section: Biochemical Precursors and Dna Binding Agentsmentioning
confidence: 99%
“…9,10 Recently o-carborane cages attached to polyamines have been made. 11 In vitro, these compounds bind to DNA and accumulate in tumor cells similarly to borocaptate (BSH) and p-borophenylalanine (BPA), which are in clinical trials. However, the cytotoxicity of carboranes prohibits their use.…”
Section: Main Group Metal Compoundsmentioning
confidence: 99%
“…14 It was observed that the toxicity strongly depended upon the number of carbon atoms in the diamine chain. To reduce this toxicity, the hydrophilic properties of the compounds were increased by exchanging the exo-amino ligand with 3-amino-1-propanol and 4-amino-1-butanol to give the desired target compounds (hydroxyalkylamine)-N-(aminoalkyl)azanonaborane (11) derivatives. The study of their structure-activity relationship with respect to their in vitro toxicities was investigated using V79 cells.…”
Section: Main Group Metal Compoundsmentioning
confidence: 99%
See 1 more Smart Citation